2019
DOI: 10.20473/fmi.v55i3.15506
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Maternal and Child Health Handbook Utilization in Surabaya, Indonesia

Abstract: Mothers and child health (MCH) are one of the main issues in family medicine. Related to this practice, Indonesian government issued mother and child health (MCH) handbook for monitoring child development due to various child developmental problems in Indonesia. However, there are reports of improper MCH handbook utilization. This study aimed to analyze factors related to the utilization of MCH handbook by mothers in Indonesia. Cross sectional observational study was conducted from March to May 2018. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…A cross-sectional observational study conducted in Surabaya on 288 parents of children aged 3-72 months sought to examine the factors that correlate with the use of the mother-child handbook. The results of that study showed that the mother's participation in an Integrated Healthcare Center was positively correlated with the use of the mother-child handbook, while the mother's age, education level, and occupation were not related to the use of the motherchild handbook [23]. Further research is needed to investigate various aspects of mothers' or parents' knowledge about the use of the mother-child handbook and its relationship to the development of children under 5 so that the mother-child handbook can be used as effectively as possible.…”
Section: Discussionmentioning
confidence: 92%
“…A cross-sectional observational study conducted in Surabaya on 288 parents of children aged 3-72 months sought to examine the factors that correlate with the use of the mother-child handbook. The results of that study showed that the mother's participation in an Integrated Healthcare Center was positively correlated with the use of the mother-child handbook, while the mother's age, education level, and occupation were not related to the use of the motherchild handbook [23]. Further research is needed to investigate various aspects of mothers' or parents' knowledge about the use of the mother-child handbook and its relationship to the development of children under 5 so that the mother-child handbook can be used as effectively as possible.…”
Section: Discussionmentioning
confidence: 92%
“…Namun minat ibu dalam membaca, memahami dan mengimplementasikan buku KIA masih belum optimal. Demikian halnya dengan kader dalam integrasi buku KIA di berbagai program belum optimal (Irwanto et al, 2019;Ambarwati, et al, 2022). Pelatihan tentang pemahaman dan implementasi buku KIA sebagai alat pemantauan pertumbuhan dan perkembangan untuk mencegah stunting pada ibu balita menjadi hal harus dilakukan untuk menurunkan angka stunting.…”
Section: Pendahuluanunclassified
“…Based on the National Health Survey in 2016, data found that 81.5% of pregnant women have MCH handbooks, but only 60.5% of pregnant women can understand it This makes one of the causes of maternal and infant mortality is ignorance of the signs of complications (8). Other research has also revealed concerns about the lack of inappropriate use of MCH handbooks by mothers/health workers (9).…”
Section: Introductionmentioning
confidence: 99%